Modelos de negocio para propiciar la conexión a red de sistemas fotovoltaicos en unidades de vivienda subsidiadas del departamento del Atlántico (2018)
This document presents the technical-operational structure of the proposed business model in order to promote of photovoltaic (PV) solar systems participation in subsidized users. A community in the city of Barranquilla was considered to evaluate its feasibility. The development of the proposal begins with the review of the state of the art of the models used as a case of success in the use of alternative energy, focusing on the promotion of photovoltaic systems under the scheme of grid-connected model. The energy market identifies requirements of the users and the subsidized regime as well as the results of the sample contemplated in order to evaluate the feasibility of implementing these technologies in the department and its urban area. In addition, the consolidation of the bibliographic analysis allowed the identification of feasible business models in other latitudes that have propitiated the connection to the final user’s network, achieving the structuring of the national and regional context to sustain the use of the distributed management model to recover the return of the investment of the photovoltaic solar energy projects. The support in the canvas model made possible the definition of the final structure considering the nine segments and evaluating the return on investment of the project in eight years with the current costs of the technology. Finally, a financial analysis is prepared to evaluate the viability and profitability of connection to the photovoltaic systems network and supporting the technical-operational structure under which the resources and services required to connect the technology are structured